PERANCANGAN APLIKASI SISTEM PAKAR DIAGNOSA KERUSAKAN HARDWARE KOMPUTER METODE FORWARD CHAINING - Rismayadi, Ali Akbar (Jurnal Informatika, 2016)
AbstractDamage to computer hardware, not a big disaster, because not all damage to computer hardware can not be repaired, nearly all computer users, whether public or institutions often suffer various kinds of damage that occurred in the computer hardware it has, and the damage can be caused by various factors that are basically as the user does not know the cause of what makes the computer hardware used damaged. Therefore, it is necessary to build an application that can help users to mendiganosa damage to computer hardware. So that everyone can diagnose the type of hardware damage his computer. Development of expert system diagnosis of damage to computer hardware uses forward chaining method by promoting alisisis descriptive of various damage data obtained from several experts and other sources of literature to reach a conclusion on the diagnosis of damage. As well as using the waterfall model as a model system development, starting from the analysis stage to stage software needs support. This application is built using a programming language tools Eclipse ADT as well as SQLite as its database. diagnosis expert system damage computer hardware is expected to be used as a tool to help find the causes of damage to computer hardware independently without the help of a computer technician.